Bacteriological profile of water samples in and around Shimla hills: a study from the sub Himalayan region - Bhagra, Suruchi; Singh, Digvijay; Sood, Atal; Kanga, Anil (International Journal Of Community Medicine And Public Health, 2017)
Background: The present study was done to assess the bacteriological quality of drinking water in and around Shimla in the event of an outbreak of hepatitis E in Shimla city, January 2016. Methods: Total 1098 water samples from different sources were received from January to July 2016. The bacteriological analysis of water was done by the multiple tube technique. Results were interpreted after 48 hours of incubation of the water sample in MacConkey bile broth medium in accordance with Mc Crady probability table. Results: A total of 1098 water samples were received in the Microbiology laboratory of which 129 (11.74%) were unsatisfactory, 25 (2.27%) satisfactory and rest 925 (84.24%) were excellent. Nearly 9.21% samples from water tanks, 2.3% from public taps were unsatisfactory but water samples from all the water ATM s were excellent. Escherichia coli were the commonest isolate 35.6%, Klebsiella pneumoniae 31.6%, Klebsiella oxytoca 19.3%, Enterobacter sps 8% and Citrobacter sps 2%. In the corresponding period 477 patients had come to the health facilities for clinical symptoms of jaundice. The serum samples from clinically suspected cases were subject to antibody testing for IgM HAV and IgM HEV and it revealed that 109 (23%) were positive for HAV while 253 (53%) were positive for HEV. During the above period 75 (15%) patients had co-infection with both HAV and HEV. Conclusions: Bacteriological assessment of drinking water is essential and should be carried out on regular basis so as to prevent outbreaks of Hepatitis A and E and other water borne diseases.